Surgical technique for the successful curative resection of locally advanced caecal cancer invading the external iliac artery: A case report. (November 2021) - Kubota, Akira; Yamazaki, Toshiyuki; Kameyama, Hitoshi; Hashidate, Hideki; Imai, Tomoyuki; Wakabayashi, Takashi
Abstract: Introduction: Curative resection generally has a good prognosis if the tumor is a locally advanced colorectal tumor. However, resection of a primary tumor that has invaded the aortoiliac artery is controversial. Herein, we report a case of successful resection of advanced cecal cancer invading the external iliac artery. Case report: A 29-year-old male patient had advanced cecal cancer invading the right external iliac artery and vein, right ureter, iliopsoas muscle, and sigmoid colon. We collected the patient's pre-/intra-/postoperative, clinical, and histological data. We reviewed the factors that may have contributed to curative resection without complications. We performed a palliative terminal ileum-sigmoid anastomosis for the prevention of intestinal obstruction. The patient received neoadjuvant chemotherapy, and the tumor patently regressed. After arterial reconstruction was performed with a femoral-femoral bypass, we performed radical resection: right hemicolectomy; partial sigmoidectomy; and partial resection of the right ureter, iliopsoas muscle, right testicular, and external iliac vessels. Pathologically, 99% of the tumor cells disappeared after chemotherapy. The patient was discharged on postoperative day 9. No recurrence has been noted 24 months after surgical resection, and the patient is receiving adjuvant chemotherapy. Conclusions: Thus, we successfully resected advanced cecal cancer without complications. Reconstruction with femoral-femoral arterial bypass and neoadjuvant chemotherapy are useful methods for curative resection without complications. Highlights: Our patient had advanced caecal cancer invading the external iliac artery. We performed reconstruction with femoral-femoral arterial bypass. The patient underwent neoadjuvant chemotherapy. We successfully resected the advanced caecal cancer without complications.